2017
DOI: 10.1007/s11936-017-0559-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Following Acute Coronary Syndrome in Women

Abstract: Acute coronary syndrome (ACS) is among the leading burdens of disease among women. It is a significant driver of morbidity and chronically undermines their quality of life. Cardiac rehabilitation (CR) is indicated for ACS patients in clinical practice guidelines, including those specifically for women. CR is a multi-component model of care, proven to reduce mortality and morbidity, including in women. However, women are significantly less likely to be referred to CR by providers, and if they are referred, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Second, in prior research, policy-makers have said that the lack of relevant research is a barrier to developing evidence-informed policies. While considerable evidence has accumulated on gendered disparities in healthcare [8][9][10][11][12][13][14][15][16][17][18], less is known about what constitutes PCCW. We synthesised research published from 2008 to 2018 that investigated PCC and included at least 50% women and identified only four studies on depression and one on cardiovascular rehabilitation [69].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, in prior research, policy-makers have said that the lack of relevant research is a barrier to developing evidence-informed policies. While considerable evidence has accumulated on gendered disparities in healthcare [8][9][10][11][12][13][14][15][16][17][18], less is known about what constitutes PCCW. We synthesised research published from 2008 to 2018 that investigated PCC and included at least 50% women and identified only four studies on depression and one on cardiovascular rehabilitation [69].…”
Section: Discussionmentioning
confidence: 99%
“…Participants referred to government policies for adults aged 18+ years. Issues referred to policies pertaining to depression or cardiac rehabilitation (or mental or cardiovascular health, more broadly), conditions with known gendered disparities in care and outcomes worldwide [8][9][10][11][12][13][14][15]. For example, compared with men, women with acute myocardial infarction underwent fewer procedures, had significantly higher risk of 30-day readmission, and were less likely to be referred for cardiac rehabilitation; additionally, women reporting depression were less likely to be referred or treated for those symptoms.…”
Section: Eligibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results found that the women in the tailored group program showed a greater reduction in depressive symptoms than women in the traditional CR group. The summary of CR benefits for women, presented in Table 1., is provided by Bennett, Lavie, and Grace (2017). Table 1 shows the benefit of CR in women.…”
Section: Benefits Of Crmentioning
confidence: 99%
“…Given the totality of evidence, however, including reductions in mortality and morbidity in nonrandomized studies, and evidence of benefit for other important outcomes such as functional capacity and quality of life, it is maintained that CR does improve outcomes in women. 4 Therefore, women should continue to be referred and encouraged to enroll and adhere to these programs. Ethically conducted trials are needed to rigorously establish the benefits of CR on mortality and morbidity in women.…”
mentioning
confidence: 99%